Erythrocyte A Peripheral Biomarker For Infection and Inflammation - Fatima Shad, Kaneez (IntechOpen, 2021)
In addition to carrying haemoglobin for gas exchange, red blood cells (RBCs) or erythrocytes contain a number of lipids, proteins, and carbohydrates, making them capable of acting as peripheral biomarkers for many pathological conditions. Early identification of key changes in erythrocytes in response to inflammatory or infectious diseases saves millions of lives worldwide. As such, this book examines the role of RBCs in immunology. Chapters cover such topics as an iron deficiency in erythrocytes, the modulation of oxidative stress (OS) in erythrocytes in bacterial and viral infections, using human foetal astrocytes (HFAs) as an experimental model to measure early predictive biomarkers for hypertension, and more.